Immunology : - Rao, C. Vaman (Alpha Science International Ltd., 2005)
Immunology: A Textbook includes recent concepts and ideas with regard to innate and acquired immunity, mucosal immune system, T-cell and B-cell activation, maturation and development, role of T-cell receptor, role of Class I MHC in auto-immune disease, kidney damage in auto-immune disease, factors involved in rheumatoid arthritis and mechanisms involved in auto-immune disease based on clinical findings. Key Features: • Immune response to disease covered in detail with recently found evidences. • Discusses various strategies in production of new vaccines against pathogens with a newer approach. • Transplantation Immunology includes recently proposed concepts on immune tolerance, T-cell anergy, NK-cell tolerance, etc. • Tumor Immunology lists newly discovered oncogenes and tumor antigens and immune therapy strategy for tumors.